Interlayer adhesive, interlayer adhesive for touch panel and touch panel
By controlling the content of alkali metal and alkaline earth metal in the interlayer adhesive of the touch panel and adding specific types of phosphate esters, the whitening problem is solved and visibility and adhesiveness is improved.
Patent Information
- Application Number
- CN202380057855.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-08
- Filing Date
- 2023-08-07
- Publication Date
- 2025-03-18
AI Technical Summary
Under the working conditions of the touch panel, especially when the temperature and humidity are high, when polyvinyl acetal resin is used as the interlayer adhesive, whitening is prone to occur, resulting in a decrease in visibility.
The content of alkali metal and alkaline earth metal is controlled to be 15 ppm or less in the resin layer of the interlayer adhesive, and contains a phosphate ester. Specifically, the HLB of the phosphate ester is 10 or less, and has a polyoxyalkylene alkyl ether group to prevent whitening.
It effectively suppresses whitening of the peripheral edge of the touch panel, improves visibility, and maintains high adhesion and impact absorption of interlayer adhesives.
Smart Images

Figure CN119654388A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an interlayer adhesive, an interlayer adhesive for a touch panel, and a touch panel. Background Art
[0002] In recent years, touch panels that enable information to be input by touching with a finger are sometimes provided in portable information terminals such as smartphones and tablets, and in-vehicle displays.
[0003] The touch panel has a multi-layer structure composed of cover glass, sensor glass, liquid crystal panel, etc. Furthermore, the transparency, brightness, contrast, etc. of the display screen are improved by filling the gaps between the layers of the components with fillers to improve visibility.
[0004] For example, Patent Document 1 discloses an invention related to an interlayer filling material for a touch panel, which is characterized in that it contains polyvinyl acetal, a reactive diluent, and a photopolymerization initiator, and records that a touch panel laminate can be obtained that has excellent followability to height differences and is not prone to cracking or breakage.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2016 / 186029 Summary of the invention
[0008] Problems to be solved by the invention
[0009] If polyvinyl acetal resin is used as a material for bonding the layers of a touch panel as described in Patent Document 1, the impact absorption is improved and cracking and breakage are not likely to occur. However, according to the research of the present inventors, it is known that if polyvinyl acetal resin is used as an interlayer adhesive for a touch panel having a sensor glass, whitening is likely to occur at the periphery of the touch panel under the operating conditions of the touch panel (when voltage is applied), especially when the temperature and humidity are high. If whitening occurs, the visibility of the touch panel is reduced, so improvement is required.
[0010] Therefore, an object of the present invention is to provide an interlayer adhesive containing a polyvinyl acetal resin and capable of suppressing whitening, and a touch panel including the interlayer adhesive.
[0011] Means for solving problems
[0012] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by an interlayer adhesive comprising a resin layer containing a polyvinyl acetal resin, wherein the content of alkali metal and alkaline earth metal contained in the resin layer is not more than a certain amount, thereby completing the present invention.
[0013] The gist of the present invention is as follows.
[0014] [1] An interlayer adhesive comprising a resin layer containing a polyvinyl acetal resin, wherein the content of an alkali metal and an alkaline earth metal contained in the resin layer is 15 ppm or less.
[0015] [2] The interlayer adhesive according to [1] above, wherein the alkali metal and alkaline earth metal contained in the resin layer is at least one metal selected from the group consisting of Na, K and Mg, and the amount of the metal is 10 ppm or less.
[0016] [3] The interlayer adhesive according to [1] or [2] above, wherein the resin layer contains a phosphoric acid ester.
[0017] [4] The interlayer adhesive according to [3] above, wherein the concentration of the phosphoric acid ester in the resin layer is 0.1% by mass or more.
[0018] [5] The interlayer adhesive according to [4] above, wherein the concentration of the phosphoric acid ester in the resin layer is 0.5 mass % or less.
[0019] [6] The interlayer adhesive according to any one of [3] to [5] above, wherein the HLB of the phosphate ester is 10 or less.
[0020] [7] The interlayer adhesive according to any one of [3] to [6] above, wherein the phosphoric acid ester has a polyoxyalkylene alkyl ether group.
[0021] [8] The interlayer adhesive according to [7] above, wherein the polyoxyalkylene alkyl ether group is a compound represented by formula (1).
[0022]
[0023] (R1 is an alkyl group having 8 to 18 carbon atoms, R2 is an alkylene group having 2 to 6 carbon atoms, n is 1 to 10, and * represents a bond)
[0024] [9] The interlayer adhesive according to any one of [3] to [8] above, wherein the phosphate ester is a compound represented by formula (2) or (3).
[0025]
[0026] (R1 is an alkyl group having 8 to 18 carbon atoms, and n is 1 to 10)
[0027]
[10] The interlayer adhesive according to any one of [3] to [9] above, wherein the phosphate ester has a dodecyl group.
[0028]
[11] The interlayer adhesive according to any one of [1] to
[10] above, wherein the polyvinyl acetal resin is a polyvinyl butyral resin.
[0029]
[12] The interlayer adhesive according to any one of [1] to
[11] above, wherein the resin layer contains a plasticizer.
[0030]
[13] An interlayer adhesive for a touch panel, comprising the interlayer adhesive according to any one of [1] to
[12] above.
[0031]
[14] A touch panel comprising the interlayer adhesive according to any one of [1] to
[12] above.
[0032] Effects of the Invention
[0033] According to the present invention, there can be provided an interlayer adhesive containing a polyvinyl acetal resin and capable of suppressing whitening, and a touch panel including the interlayer adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic cross-sectional view showing one embodiment of the touch panel of the present invention.
[0035] Figure 2 It is a schematic cross-sectional view showing another embodiment of the touch panel of the present invention.
[0036] <Interlayer adhesive>
[0037] The interlayer adhesive of the present invention comprises a resin layer containing a polyvinyl acetal resin, wherein the content of an alkali metal and an alkaline earth metal contained in the resin layer is 15 ppm or less.
[0038] [Alkali metal and alkaline earth metal content]
[0039] The content of alkali metal and alkaline earth metal in the resin layer of the present invention is 15 ppm or less. If the content of alkali metal and alkaline earth metal exceeds 15 ppm, whitening of the peripheral portion cannot be suppressed when used for bonding of a touch panel.
[0040] From the viewpoint of further suppressing whitening, the content of the alkali metal and alkaline earth metal in the resin layer is preferably 10 ppm or less, more preferably 5 ppm or less, and even more preferably 3 ppm or less.
[0041] The reason why whitening can be suppressed is not clear, but it is presumed that since alkali metals and alkaline earth metals serve as nuclei, water is easily aggregated, and thus the aggregation of water can be suppressed by reducing the amount of these metals.
[0042] Furthermore, the content of alkali metals and alkaline earth metals in the resin layer is ideally 0 ppm from the viewpoint of suppressing whitening, but is preferably 0.1 ppm or more, more preferably 0.5 ppm or more from the viewpoint of suppressing coloration such as yellowing of the resin layer.
[0043] The so-called alkali metals refer to Li (lithium), Na (sodium), K (potassium), Rb (rubidium) and Cs (cesium) among the elements of Group 1 of the periodic table, and the so-called alkaline earth metals refer to Be (beryllium), Mg (magnesium), Ca (calcium), Sr (strontium) and Ba (barium) among the elements of Group 2.
[0044] The content of alkali metal and alkaline earth metal refers to the total content of alkali metal and alkaline earth metal in the resin layer. In addition, the unit "ppm" of content in this specification is a mass basis and means "mass ppm".
[0045] The content of the alkali metal and alkaline earth metal can be adjusted to a desired value by adjusting the production method of the polyvinyl acetal resin, the type and amount of additives blended in the resin layer, and the like.
[0046] The alkali metal and alkaline earth metal contained in the resin layer of the present invention is at least one metal selected from Na, K and Mg, and the amount of the above metal is preferably 10 ppm or less, more preferably 5 ppm or less, and further preferably 3 ppm or less. It should be noted that the above-mentioned metal amount refers to the total amount of Na, K and Mg.
[0047] By adjusting the amounts of these specific alkali metals and alkaline earth metals to a certain level or less, whitening of the sensor glass can be more effectively suppressed.
[0048] In addition, the amount of the alkali metal and the alkaline earth metal in the resin layer can be measured by ICP emission spectrometry as described in Examples below.
[0049] [Phosphate ester]
[0050] The resin layer of the present invention preferably contains a phosphate. By further containing a phosphate on the basis of adjusting the content of the alkali metal and alkaline earth metal contained in the resin layer to a certain value or less as described above, the whitening of the peripheral portion can be more effectively suppressed when used for bonding of a touch panel. The reason is unclear, but it can be considered that it is because the phosphate is easy to adsorb the alkali metal and the alkaline earth metal, so by reducing the amount of the alkali metal and the alkaline earth metal while containing the phosphate, the aggregation of water can be effectively suppressed.
[0051] Phosphate esters are compounds having a phosphate ester structure such as phosphate monoesters, phosphate diesters, and phosphate triesters, wherein all or part of the three hydrogen atoms in phosphoric acid (O=P(OH)3) are replaced by organic groups. Among them, compounds having the function of a surfactant having a hydrophilic part and a lipophilic part are preferred, and phosphate monoesters and phosphate diesters are preferred.
[0052] From the viewpoint of further suppressing whitening, the HLB (Hydrophilic-Lipophilic Balance) of the phosphoric acid ester in the present invention is preferably 13 or less, more preferably 11 or less, further preferably 10 or less, and is preferably 4 or more, more preferably 6 or more.
[0053] It should be noted that the "HLB" in the present invention can be calculated by the Griffith method [HLB=20×(MW / MO), MW: the total formula weight of the hydrophilic part, MO: molecular weight].
[0054] From the viewpoint of making the HLB to a desired value and effectively suppressing whitening, the phosphoric acid ester in the present invention preferably has a polyoxyalkylene alkyl ether group, and more specifically, is preferably a compound having a polyoxyalkylene alkyl ether group and a phosphoric acid skeleton.
[0055] The polyoxyalkylene alkyl ether group is a group in which a polyoxyalkylene group and an alkyl group are connected via an ether bond (—O—), and has a structure represented by formula (1).
[0056]
[0057] (R1 is an alkyl group, R2 is an alkylene group, n is 1 to 50, and * represents a bond)
[0058] R1 is preferably an alkyl group having 6 to 20 carbon atoms, more preferably an alkyl group having 8 to 18 carbon atoms, and still more preferably an alkyl group having 10 to 14 carbon atoms. R1 may be a linear alkyl group or a branched alkyl group, but is preferably a linear alkyl group from the viewpoint of further suppressing whitening.
[0059] R1 can include, for example, hexyl, isohexyl, heptyl, isoheptyl, octyl, 2-ethylhexyl, isooctyl, nonyl, isononyl, decyl, isodecyl, undecyl, isoundecyl, dodecyl, isododecyl, tridecyl, isotridecyl, tetradecyl, isotetradecyl, pentadecyl, isopentadecyl, hexadecyl, isohexadecyl, 2-hexyldecyl, heptadecyl, isoheptadecyl, octadecyl, isooctadecyl, 2-octyldecyl, 2-hexyldodecyl, nonadecyl, isononadecyl, eicosyl, isoeicosyl and the like.
[0060] Among them, R1 is preferably dodecyl or isotridecyl, and more preferably dodecyl. That is, as a phosphate ester, from the viewpoint of adjusting the HLB to a desired range and further suppressing whitening, it is preferably dodecyl or isotridecyl, and more preferably dodecyl.
[0061] In the above formula (1), R2 is an alkylene group, preferably an alkylene group having 2 to 6 carbon atoms, more preferably an alkylene group having 2 to 3 carbon atoms, and further preferably an alkylene group having 2 carbon atoms (i.e., ethylene group). In addition, when n is 2 or more, multiple R2 groups may be the same or different.
[0062] n is 1-50, preferably 1-30, more preferably 1-10.
[0063] In formula (1), * represents a bond, and * is preferably a bond to a phosphorus atom of a phosphate skeleton.
[0064] In the present invention, the phosphate ester is preferably a compound represented by the following formula (2) or formula (3), and more preferably a compound represented by formula (2). In addition, the phosphate ester in the present invention may be a mixture of compounds represented by formula (2) and formula (3).
[0065]
[0066] In formula (2) and formula (3), R1 and n have the same meanings as in formula (1).
[0067] From the viewpoint of further suppressing whitening, the content of the phosphate ester in the resin layer is preferably 0.04 mass % or more, more preferably 0.1 mass % or more, and from the viewpoint of heat yellowing resistance, is preferably 0.5 mass % or less, more preferably 0.3 mass % or less.
[0068] [Polyvinyl acetal resin]
[0069] The resin layer of the present invention contains a polyvinyl acetal resin. By containing the polyvinyl acetal resin, the adhesion between the various members constituting the touch panel, such as the cover glass and the sensor glass, can be improved, and the impact absorption is improved, and cracks and breakages are less likely to occur.
[0070] The polyvinyl acetal resin is obtained by acetalizing polyvinyl alcohol (PVA) with an aldehyde. That is, the polyvinyl acetal resin is preferably an acetalized product of polyvinyl alcohol (PVA). Polyvinyl alcohol (PVA) is obtained, for example, by saponifying a polyvinyl ester such as polyvinyl acetate. The saponification degree of polyvinyl alcohol is generally 70 to 99.9 mol%. The polyvinyl acetal resin may be used alone or in combination of two or more.
[0071] The average degree of polymerization of the polyvinyl acetal resin is preferably 200 or more, more preferably 500 or more, further preferably 1000 or more, and further preferably 1500 or more. The average degree of polymerization of the polyvinyl acetal resin is preferably 5000 or less, more preferably 4000 or less, and further preferably 3500 or less.
[0072] The average degree of polymerization of the polyvinyl acetal resin is the same as the average degree of polymerization of PVA serving as a raw material of the polyvinyl acetal resin, and the average degree of polymerization of PVA is determined by a method in accordance with JIS K6726 "Polyvinyl Alcohol Test Method (Polyvinyl Alcohol Test Method)".
[0073] The aldehyde used for acetalization is not particularly limited, but an aldehyde having 1 to 10 carbon atoms is preferably used, an aldehyde having 3 to 5 carbon atoms is more preferably used, an aldehyde having 4 or 5 carbon atoms is further preferably used, and an aldehyde having 4 carbon atoms is particularly preferably used.
[0074] The aldehyde having 1 to 10 carbon atoms is not particularly limited, and examples thereof include formaldehyde, acetaldehyde, propionaldehyde, n-butyraldehyde, isobutyraldehyde, n-valeraldehyde, 2-ethylbutyraldehyde, n-hexanal, n-octanal, n-nonanal, n-decanal, and benzaldehyde. Among them, acetaldehyde, propionaldehyde, n-butyraldehyde, isobutyraldehyde, n-hexanal, or n-valeraldehyde is preferred, propionaldehyde, n-butyraldehyde, isobutyraldehyde, or n-valeraldehyde is more preferred, n-butyraldehyde or n-valeraldehyde is further preferred, and n-butyraldehyde is most preferred. The aldehydes may be used alone or in combination of two or more.
[0075] The number of carbon atoms in the acetal group contained in the polyvinyl acetal resin is not particularly limited, but is preferably 1 to 10, more preferably 3 to 5, further preferably 4 or 5, and particularly preferably 4. Specifically, the acetal group is particularly preferably a butyral group, and therefore, the polyvinyl acetal resin is preferably a polyvinyl butyral resin.
[0076] The hydroxyl amount of the polyvinyl acetal resin is preferably 15 mol% or more, and preferably 38 mol% or less. By making the hydroxyl amount 15 mol% or more, the adhesion is easy to become good. In addition, by making the hydroxyl amount 38 mol% or less, the resin layer is prevented from becoming too hard. From the viewpoint of adhesion, the above-mentioned hydroxyl amount is more preferably 20 mol% or more, and more preferably 25 mol% or more. In addition, the above-mentioned hydroxyl amount is more preferably 35% or less, and more preferably 33 mol% or less.
[0077] When a polyvinyl butyral resin is used as the polyvinyl acetal resin, from the same viewpoint, the hydroxyl group amount is 15 mol% or more, and is preferably 38 mol% or less, more preferably 20 mol% or more, further preferably 25 mol% or more, more preferably 35 mol% or less, and further preferably 33 mol% or less.
[0078] The hydroxyl content of the polyvinyl acetal resin is a value expressed as a percentage of the molar fraction obtained by dividing the amount of ethylene groups bonded to the hydroxyl groups by the total amount of ethylene groups in the main chain. The hydroxyl content of the ethylene groups bonded to the hydroxyl groups can be measured, for example, according to JIS K6728 "Polyvinyl Butyral Test Method (Polyvinyl Butyral Test Method)".
[0079] The degree of acetalization of the polyvinyl acetal resin is preferably 47 mol% or more, and preferably 85 mol% or less. The degree of acetalization is more preferably 55 mol% or more, and further preferably 60 mol% or more, and further preferably 80 mol% or less, and further preferably 75 mol% or less.
[0080] In addition, when the acetal group is a butyral group and the polyvinyl acetal resin is a polyvinyl butyral resin, the acetalization degree means the butyralization degree.
[0081] The above-mentioned acetalization degree is a value of the molar fraction obtained by subtracting the amount of ethylene bonded to a hydroxyl group and the amount of ethylene bonded to an acetyl group from the total amount of ethylene bonded to the main chain and dividing the value obtained by dividing the total amount of ethylene bonded to the main chain by a percentage. The acetalization degree (butyralization degree) is preferably calculated from the result of measurement by a method according to JIS K6728 "Polyvinyl Butyral Test Method (Polyvinyl Butyral Test Method)".
[0082] The degree of acetylation of the polyvinyl acetal resin is preferably 30 mol% or less, more preferably 20 mol% or less, further preferably 10 mol% or less, and further preferably 2 mol% or less. If the degree of acetylation is below the upper limit, the moisture resistance of the resin layer becomes high. In addition, the degree of acetylation is not particularly limited, but is preferably 0.01 mol% or more, and more preferably 0.1 mol% or more.
[0083] The acetylation degree is a value expressed as a percentage of the molar fraction obtained by dividing the amount of ethylene groups bonded to the acetyl group by the total amount of ethylene groups in the main chain. The amount of ethylene groups bonded to the acetyl group can be measured, for example, according to JIS K6728 "Polyvinyl Butyral Test Method (Polyvinyl Butyral Test Method)".
[0084] [Method for producing polyvinyl acetal resin]
[0085] The polyvinyl acetal resin is obtained by acetalizing polyvinyl alcohol (PVA) with an aldehyde as described above. The acetalization is usually carried out in the presence of an acid catalyst. Examples of the acid catalyst include inorganic acids such as hydrochloric acid, sulfuric acid, and nitric acid, and organic acids such as acetic acid, benzoic acid, p-toluenesulfonic acid, uric acid, and barbituric acid. These acids may be used alone or in combination of two or more.
[0086] In addition, if the acid catalyst remains in the polyvinyl acetal resin, it becomes the cause of discoloration such as yellowing, so it is preferably neutralized with a neutralizing agent. As the neutralizing agent, sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, potassium bicarbonate, etc. can be mentioned, among which sodium bicarbonate or potassium bicarbonate are preferred. As the neutralizing agent, generally speaking, a compound containing an alkali metal is used as described above. Therefore, from the viewpoint of making the content of the alkali metal and alkaline earth metal in the resin layer to be below a certain level, the preferred amount of the neutralizing agent is suppressed to a small amount as much as possible.
[0087] The amount of the neutralizer used relative to the polyvinyl acetal resin is preferably 0.1 to 5% by mass, more preferably 0.3 to 3% by mass, and even more preferably 0.5 to 1.5% by mass, relative to 100% by mass of the polyvinyl acetal resin.
[0088] [Other resins]
[0089] The resin layer may contain resins other than the polyvinyl acetal resin within the scope of not impairing the effect of the present invention. As resins other than the polyvinyl acetal resin, for example, ethylene-vinyl acetate copolymer resins, ionomer resins, polyurethane resins, thermoplastic elastomers, acrylic resins, etc. can be cited. Based on the total amount of resins included in the resin layer, the content of the polyvinyl acetal resin is preferably 50% by mass or more, more preferably 80% by mass or more, and further preferably 100% by mass.
[0090] [Plasticizer]
[0091] The resin layer of the present invention preferably contains a plasticizer. By including a plasticizer in the resin layer together with the polyvinyl acetal resin, the impact absorption can be further improved. In addition, the resin layer contains a plasticizer, thereby becoming softer and easier to adjust to a predetermined shape.
[0092] As the plasticizer, for example, organic phosphorus plasticizers such as organic ester plasticizers, organic phosphate plasticizers and organic phosphite plasticizers, organic ether plasticizers such as polyalkylene glycol plasticizers and polyoxyalkylene ether plasticizers, alcohol plasticizers, etc. can be cited. One type of plasticizer can be used alone, or two or more types can be used in combination. Among the above, organic ester plasticizers and polyalkylene glycol plasticizers are preferred, and organic ester plasticizers are more preferred. As preferred organic ester plasticizers, monobasic organic acid esters and polybasic organic acid esters, etc. can be cited.
[0093] As the monobasic organic acid ester, esters formed by diols and monobasic organic acids can be mentioned. As the diol, polyalkylene glycols can be mentioned in which each alkylene unit has 2 to 4 carbon atoms, preferably 2 or 3 carbon atoms, and the number of repetitions of the alkylene units is 2 to 10, preferably 2 to 4. In addition, as the diol, monoalkylene glycols (i.e., the number of repetition units is 1) can be mentioned in which each alkylene unit has 2 to 4 carbon atoms, preferably 2 or 3 carbon atoms.
[0094] Specific examples of the diol include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, tetrapropylene glycol, and butylene glycol.
[0095] Examples of the monobasic organic acid include organic acids having 3 to 10 carbon atoms, and specific examples thereof include butyric acid, isobutyric acid, hexanoic acid, 2-ethylbutyric acid, heptanoic acid, n-octanoic acid, 2-ethylhexanoic acid, n-nonanoic acid, and decanoic acid.
[0096] Specific examples of the monobasic organic acid ester include triethylene glycol di-2-ethylbutyrate, triethylene glycol di-2-ethylhexanoate, triethylene glycol dioctanoate, triethylene glycol di-n-octanoate, triethylene glycol di-n-heptanoate, tetraethylene glycol di-n-heptanoate, tetraethylene glycol di-2-ethylhexanoate, diethylene glycol di-2-ethylbutyrate, diethylene glycol di-2-ethylhexanoate, dipropylene glycol di-2-ethylbutyrate, triethylene glycol di-2-ethylvalerate, tetraethylene glycol di-2-ethylbutyrate, diethylene glycol dicaprate, triethylene glycol di-n-heptanoate, tetraethylene glycol di-n-heptanoate, triethylene glycol di-2-ethylbutyrate, ethylene glycol di-2-ethylbutyrate, 1,2-propylene glycol di-2-ethylbutyrate, 1,3-propylene glycol di-2-ethylbutyrate, 1,4-butylene glycol di-2-ethylbutyrate, and 1,2-butylene glycol di-2-ethylbutyrate.
[0097] Examples of polybasic organic acid esters include ester compounds formed by dibasic organic acids having 4 to 12 carbon atoms, such as adipic acid, sebacic acid, azelaic acid, and phthalic acid, and alcohols having 4 to 10 carbon atoms. The alcohols having 4 to 10 carbon atoms may have a linear chain, a branched chain structure, or a cyclic structure.
[0098] Specifically, dibutyl sebacate, dioctyl azelate, dihexyl adipate, dioctyl adipate, hexylcyclohexyl adipate, hexylcyclohexyl adipate, diisononyl adipate, heptylnonyl adipate, dibutyl carbitol adipate, mixed adipate, dioctyl phthalate, dibutyl phthalate, etc. can be mentioned. In addition, oil-modified sebacic acid alcohol acid, etc. can be mentioned. As mixed adipate, adipate made from two or more alcohols selected from alkyl alcohols having 4 to 9 carbon atoms and cyclic alcohols having 4 to 9 carbon atoms can be mentioned.
[0099] The organic ester plasticizer is not limited to the complete ester of the above esters, and may be a partial ester. For example, it may be a partial ester formed by a glycol and a monobasic organic acid, or it may be a partial ester formed by a dibasic organic acid and an alcohol. Specifically, triethylene glycol mono-2-ethylhexanoate and the like may be cited.
[0100] Furthermore, partial esters of trivalent or higher alcohols such as glycerol and monovalent organic acids may be used. Examples of the monovalent organic acid include monovalent organic acids having 3 to 24 carbon atoms, preferably 6 to 18 carbon atoms. Specific examples of partial esters of trivalent or higher alcohols and monovalent organic acids include mono- or diesters of glycerol and stearic acid, and mono- or diesters of glycerol and 2-ethylhexanoic acid.
[0101] As the organic ester plasticizer, among the above, triethylene glycol di-2-ethylhexanoate (3GO) and dioctyl adipate (DOA) are particularly preferably used.
[0102] Examples of the organic phosphorus plasticizer include phosphoric acid esters such as tributoxyethyl phosphate, isodecyl diphenyl phosphate, and triisopropyl phosphate.
[0103] Examples of the polyalkylene glycol plasticizer include polyethylene glycol, polypropylene glycol, poly(ethylene oxide / propylene oxide) block copolymers, poly(ethylene oxide / propylene oxide) random copolymers, and polybutylene glycol. Among these, polypropylene glycol is preferred.
[0104] The polyoxyalkylene ether plasticizer is an ether compound of a monohydric or polyhydric alcohol and a polyoxyalkylene group.
[0105] Specific examples of the polyoxyalkylene ether plasticizer include polyoxyethylene hexyl ether, polyoxyethylene heptyl ether, polyoxyethylene octyl ether, polyoxyethylene-2-ethylhexyl ether, polyoxyethylene nonyl ether, polyoxyethylene decyl ether, polyoxyethylene allyl ether, polyoxypropylene allyl ether, polyoxyethylene glyceryl ether, polyoxypropylene glyceryl ether, polyoxyethylene diglyceryl ether, polyoxypropylene diglyceryl ether, polyoxyalkylene pentaerythritol ether, and polycaprolactone triol.
[0106] The polyoxyalkylene ether plasticizer is preferably an ether compound of a polyhydric alcohol and a polyoxyalkylene group, more preferably an ether compound of glycerol or diglycerol and a polyoxyalkylene group, and still more preferably an ether compound of glycerol or diglycerol and a polyoxypropylene group.
[0107] As alcohol plasticizers, alcohols other than polyalkylene glycol plasticizers and polyoxyalkylene ether plasticizers can be cited. Specifically, various polyols such as ethylene glycol, propylene glycol, butylene glycol, hexylene glycol, trimethylolpropane, pentaerythritol, glycerol, and diglycerol can be cited. Among them, ethylene glycol is preferred.
[0108] The content of the plasticizer in the resin layer is preferably 5 parts by mass or more, more preferably 15 parts by mass or more, further preferably 30 parts by mass or more, further preferably 100 parts by mass or less, more preferably 60 parts by mass or less, further preferably 50 parts by mass or less, based on 100 parts by mass of the polyacetal resin.
[0109] [Adhesion regulator]
[0110] From the viewpoint of improving the adhesive force, the resin layer in the present invention may contain an adhesive force regulator. However, as the adhesive force regulator, since compounds containing alkali metals or alkaline earth metals are generally used, from the viewpoint of making the content of alkali metals and alkaline earth metals contained in the resin layer below a certain level, it is preferred to use as little adhesive force regulator as possible.
[0111] When an adhesion modifier is used, its content is such that the content of alkali metal and alkaline earth metal in the resin layer containing polyvinyl acetal is 15 ppm or less, preferably 10 ppm or less, more preferably 5 ppm or less, and further preferably 3 ppm or less.
[0112] In the present invention, it is preferred that the resin layer does not contain an adhesion modifier.
[0113] As the adhesion modifier, metal salts of organic acids such as carboxylic acids can be mentioned. As the organic acid, for example, carboxylic acids having 2 to 10 carbon atoms can be mentioned, and as the metal salt, potassium salts, sodium salts, magnesium salts can be mentioned. If the adhesion modifier is specifically exemplified, magnesium acetate, magnesium propionate, magnesium 2-ethylbutyrate, magnesium 2-ethylhexanoate, etc. can be mentioned.
[0114] [Other additives]
[0115] The resin layer of the present invention may contain known additives such as tackifier resin, emulsifier, softener, fine particles, filler, pigment, dye, silane coupling agent, antioxidant, surfactant, wax, etc. as needed.
[0116] (Film shape)
[0117] From the viewpoint that it can be easily attached to a substrate, the interlayer adhesive of the present invention is preferably in the form of a film. In this case, the interlayer adhesive of the present invention can be obtained by, for example, mixing resin, phosphate ester and various additives mixed as required, extruding the resulting resin composition, pressing molding, etc.
[0118] [thickness]
[0119] The thickness of the interlayer adhesive of the present invention is not particularly limited, and can be appropriately adjusted according to the size and type of the touch panel used. The thickness of the interlayer adhesive is preferably 0.05 mm or more, more preferably 0.1 mm or more, and further preferably 0.15 mm or more, and preferably 5 mm or less, more preferably 3 mm or less, and further preferably 1 mm or less.
[0120] [Touch panel]
[0121] The interlayer adhesive of the present invention can be suitably used for bonding the members constituting a touch panel to each other. In addition, the present invention can provide a touch panel including the interlayer adhesive.
[0122] An interlayer adhesive for a touch panel using such an interlayer adhesive of the present invention is also one of the present invention.
[0123] Figure 1 One embodiment of the touch panel of the present invention is shown in FIG. It should be noted that the present invention is not limited to the contents of the drawings.
[0124] Figure 1 The touch panel 10 shown in the figure has a cover glass 11, a sensor glass 12, and a liquid crystal panel 13 in sequence. The cover glass 11 is a light-transmitting member, and its surface is an operation surface that is contacted by a user's finger or the like in conjunction with a touch operation. The sensor glass 12 has an ITO pattern (not shown) formed on its surface, thereby being able to detect a touch operation of a user's finger (detection object). It should be noted that the sensor glass 12 can be a single-layer structure or a multi-layer structure. In addition, a predetermined image can be displayed by the liquid crystal panel 13. It should be noted that an organic EL panel can be used instead of the liquid crystal panel 13.
[0125] The interlayer adhesive 14 of the present invention is provided between the cover glass 11 and the sensor glass 12 to bond and fix the cover glass 11 and the sensor glass 12. Since polyvinyl acetal resin is used in the interlayer adhesive 14, the adhesion between the cover glass 11 and the sensor glass 12 is good, and the impact absorption is improved, and cracks and breakages are not easily generated.
[0126] Furthermore, by setting the content of alkali metal and alkaline earth metal in the resin layer constituting the interlayer adhesive 14 to a certain level or less, whitening can be suppressed even when the temperature and humidity are high under the operating conditions of the touch panel (when voltage is applied).
[0127] In addition, if Figure 1 As shown, the interlayer adhesive 14 of the present invention may be used between the sensor glass 12 and the liquid crystal panel 13 as necessary, but a generally used optical adhesive (OCA) or the like may also be used.
[0128] It should be noted that in Figure 1 In FIG. 1 , a touch panel composed of a cover glass 11 , a sensor glass 12 , a liquid crystal panel 13 , and an interlayer adhesive 14 is shown, but a touch panel having a structure other than these may also be used.
[0129] In addition, if Figure 2 As shown, the touch panel 2 may include a touch panel body 100 and a cover member 151 .
[0130] The cover member 151 includes a first member 61 made of a glass plate, an interlayer adhesive 65, and a second member 160. The interlayer adhesive 65 is arranged in close contact with the second surface 61B with substantially uniform thickness. The second member 160 is arranged in close contact with the interlayer adhesive 65 along the outer surface of the interlayer adhesive 65. The second member 160 is arranged to follow the outer surface of the interlayer adhesive 65.
[0131] The first member 61 has a first surface 61A and a second surface 61B opposite to the first surface 61A. The so-called operation surface is the first surface 61A. A transparent interlayer adhesive 65 is disposed on the entire surface of the second surface 61B.
[0132] The material of the first member 61 is, for example, a glass plate, which may be a flexible thin plate glass. As the first member 61, from the viewpoint of weight reduction, it is preferable to use a glass plate with a thickness of 0.01 mm or more and 0.55 mm or less. When constituting a cover member 151 with a size of 25 inches or more, it is preferable to use a glass plate with a thickness of 0.01 mm or more and 1.85 mm or less.
[0133] In addition, if a glass plate with a thickness of 0.7 mm or less is used, a thin cover member 151 can be formed. For the cover member 151 corresponding to the touch panel body 100 applicable to a large screen of 25 inches or more, in order to avoid bending of the earth, it is desirable to use a thick glass plate as the first member 61, but from the perspective of the overall thickness, the thickness of the first member 61 is preferably 2.5 mm or less.
[0134] The material of the second member 160 is, for example, a glass plate, which may be a flexible thin plate glass. From the perspective of weight reduction, it is preferred to use a glass plate with a thickness of 0.01 mm or more and 0.55 mm or less as the second member 160. When constituting a cover member 151 having a size of 25 inches or more, it is preferred to use a glass plate with a thickness of 0.01 mm or more and 1.85 mm or less. If a glass plate of this thickness is used, as the second member 160, it can be easily arranged following the outer surface of the interlayer adhesive 65, and the entry of bubbles and the like is also suppressed.
[0135] The covering member 151 is configured by arranging a first member 61 made of a glass plate and a second member 160 made of a glass plate with an interlayer adhesive 65 interposed therebetween.
[0136] The touch panel body 100 is mounted on the outer surface of the second member 160. Figure 2 , a touch panel body 100 having a structure in which two substrates are stacked is illustrated. If the touch panel body 100 is simply described, the touch panel body 100 includes a first substrate 111 and a second substrate 112. The first substrate 111 and the second substrate 112 are transparent, and are made of, for example, a resin film or a glass plate. The first substrate 111 is provided with a transmitting electrode of a sensor electrode, and the second substrate 112 is provided with a receiving electrode of a sensor electrode. The first substrate 111 and the second substrate 112 are bonded together by a transparent adhesive 115. Furthermore, a transparent adhesive 116 used when adhering to the covering member 151 is provided on the second substrate 112. The touch panel body 100 is mounted on the outer surface of the second member 160 via the adhesive 116. For the adhesive 115 and the adhesive 116, the interlayer adhesive according to the present invention can be used, but a generally used optical adhesive (OCA) or the like can also be used.
[0137] The manufacturing method of the touch panel of the present invention is not particularly limited, but it is preferably manufactured by vacuum packaging. For example, an interlayer adhesive is introduced between part or all of the components constituting the touch panel, added to a vacuum package, and after vacuum suction, pre-bonded at about 70 to 110° C. to obtain a laminate. Next, the laminate is added to an autoclave, or pressed, and pressed at about 120 to 150° C. and a pressure of 1 to 1.5 MPa. In this way, a touch panel can be obtained. Example
[0138] The present invention will be described in further detail by way of examples, but the present invention is not limited to these examples at all.
[0139] In addition, the measurement and evaluation of various physical properties were performed as follows.
[0140] [Content of alkali metals and alkaline earth metals]
[0141] The total content of alkali metals and alkaline earth metals contained in the resin layer was quantified by ICP emission element analysis. ICP emission element analysis is performed by heating and decomposing the sample with sulfuric acid and nitric acid, and then the decomposed product is fixed to volume with ultrapure water, and then the ICP-AES method using an ICP-AES emission element analyzer (ICAP-575 manufactured by Japan Jiale Asia Co., Ltd.) is used.
[0142] [Whitening distance based on heat and humidity resistance test]
[0143] The cover glass laminates prepared in each example and comparative example were maintained at a temperature of 60°C and a relative humidity of 90% while applying a voltage (5V) by a function generator, and the whitening distance after 1000 hours was measured. The whitening distance was obtained by measuring the distance from the whitened portion to the edge of the cover glass laminate, and was evaluated according to the following criteria.
[0144] (Evaluation Criteria)
[0145] AA: Whitening distance is within 1.5mm
[0146] A: The whitening distance is more than 1.5mm and less than 3mm
[0147] C: Whitening distance exceeds 3mm
[0148] The plasticizer, phosphate ester, and adhesion modifier used in Examples and Comparative Examples are as follows.
[0149] <Plasticizer>
[0150] 3GO: Triethylene glycol di-2-ethylhexanoate
[0151] <Phosphate ester>
[0152] "Platinum A208B" manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd. is a compound in which, in the formula (2), R1 is a dodecyl group and n is 2. HLB=8.
[0153] <Adhesion modifier>
[0154] Magnesium acetate aqueous solution (Mg concentration 3.65wt%)
[0155] [Example 1]
[0156] (Manufacture of polyvinyl butyral resin)
[0157] In a reactor equipped with a stirring device, 1800g of ion exchange water and 200g of polyvinyl alcohol A (average degree of polymerization 1700, saponification degree 99 mol%) were added, and the mixture was heated and dissolved while stirring to obtain a polyvinyl alcohol solution. Next, 25% hydrochloric acid was added as a catalyst in a manner that the hydrochloric acid concentration became 0.2% by mass in the solution, and after adjusting the temperature to 15°C, 16g of normal butyraldehyde was added while stirring. Then, 95g of normal butyraldehyde was added, and as a result, white granular polyvinyl alcohol butyral resin was precipitated. 25% hydrochloric acid was added 10 minutes after precipitation to a concentration of 1.8% by weight, and heated to 63°C and maintained for 2 hours. Then, the solution was cooled, washed with excess water and rinsed with unreacted butyraldehyde.
[0158] Next, the polyvinyl butyral resin obtained above and ion exchange water were added in a reactor equipped with a stirring device so that the slurry concentration became 10wt%. Furthermore, sodium bicarbonate as a general neutralizing agent was added in an amount of 1 mass % relative to the polyvinyl butyral resin, heated to 80°C to neutralize the hydrochloric acid catalyst, cooled, washed with excess water, and dried to obtain the polyvinyl butyral resin. The obtained polyvinyl butyral resin had a hydroxyl content of 30.6 mol%, an acetalization degree of 68.7 mol%, and an acetylation degree of 0.7 mol%.
[0159] (Manufacturing of interlayer adhesive)
[0160] 100 parts by mass of the polyvinyl butyral resin and 35 parts by mass of 3GO as a plasticizer were mixed and fully melt-kneaded using a mixing roll, and then press-molded using a press molding machine at 150° C. for 10 minutes to obtain an interlayer adhesive having a thickness of 0.4 mm.
[0161] (evaluate)
[0162] Cover glass (soda glass manufactured by Nippon Sheet Glass Co., Ltd.) and sensor glass on which an ITO pattern was formed (manufactured by Technoprene Co., Ltd., ITO thickness 150 nm, resistance value about 10Ω / □) were prepared.
[0163] The interlayer adhesive prepared as described above was sandwiched between the sensor glass and the cover glass to obtain a laminate. The laminate was placed in a rubber bag and degassed at a vacuum of 1.0 MPa for 10 minutes. The laminate was then transferred to an oven at a temperature of 100°C in a degassed state and temporarily pressed until the temperature reached 85°C. The temporarily pressed laminate was pressed for 20 minutes at 140°C and a pressure of 1.3 MPa in an autoclave to obtain a cover glass laminate in which the cover glass, the resin layer (interlayer adhesive for the touch panel), and the sensor glass were sequentially laminated.
[0164] The amount of alkali metal and alkaline earth metal in the resin layer of the cover glass laminate was evaluated as described above. In addition, the whitening distance of the cover glass laminate was measured as described above. The results are shown in Table 1.
[0165] [Example 2]
[0166] In the production of the polyvinyl butyral resin of Example 1, the same procedure as in Example 1 was carried out except that the type of the neutralizing agent was changed from sodium bicarbonate to potassium bicarbonate.
[0167] [Example 3]
[0168] In the production of the interlayer adhesive of Example 1, the same procedure as in Example 1 was carried out except that 0.018 parts by mass of a magnesium acetate aqueous solution was added as an adhesion modifier to 100 parts by mass of the polyvinyl butyral resin.
[0169] [Example 4]
[0170] In the production of the interlayer adhesive of Example 1, the same procedure as in Example 1 was carried out except that 0.14 parts by mass of Primer A208B as a phosphate ester was added to 100 parts by mass of the polyvinyl butyral resin.
[0171] [Comparative Example 1]
[0172] In the production of the polyvinyl butyral resin of Example 1, the same procedure as in Example 1 was carried out except that the amount of the neutralizing agent was 10 times the equivalent (that is, 10% by mass relative to the polyvinyl butyral resin).
[0173] [Comparative Example 2]
[0174] In the production of the polyvinyl butyral resin of Example 2, the same procedure as in Example 2 was carried out except that the amount of the neutralizing agent was 10 times the equivalent (that is, 10% by mass relative to the polyvinyl butyral resin).
[0175] [Comparative Example 3]
[0176] In the production of the interlayer adhesive of Example 3, the same procedures as in Example 3 were carried out except that the amount of the magnesium acetate aqueous solution as the adhesion modifier was 3 times (ie, 0.054 parts by mass with respect to 100 parts by mass of the polyvinyl butyral resin).
[0177] [Table 1]
[0178] Table 1
[0179]
[0180] ※ The PVB, plasticizer, and adhesion modifier in Table 1 are expressed in parts by mass. The content of phosphate ester is expressed in mass % in the resin layer.
[0181] As described above, by using the interlayer adhesive of each Example having a small amount of alkali metal and alkaline earth metal, whitening of the touch panel in the moisture and heat resistance test was suppressed.
[0182] On the other hand, the interlayer adhesives of the comparative examples contained a large amount of alkali metal and alkaline earth metal, and the whitening of the touch panel in the moisture and heat resistance test was not suppressed.
[0183] Explanation of symbols
[0184] 2.10 Touch Panel
[0185] 11 Cover glass
[0186] 12 Sensor glass
[0187] 13 LCD Panel
[0188] 14 Interlayer adhesive
[0189] 61 First Component
[0190] 65 interlayer adhesive
[0191] 100 Touch panel body
[0192] 111 First Substrate
[0193] 112 Second substrate
[0194] 115, 116 Adhesive
[0195] 151 Covering Components
[0196] 160 Second component.
Claims
1. An interlayer adhesive comprising a resin layer containing a polyvinyl acetal resin, wherein the content of alkali metal and alkaline earth metal contained in the resin layer is 15 ppm or less. 2 . The interlayer adhesive according to claim 1 , wherein the alkali metal and alkaline earth metal contained in the resin layer is at least one metal selected from the group consisting of Na, K and Mg, and the amount of the metal is 10 ppm or less. The interlayer adhesive according to claim 1 or 2, wherein the resin layer contains a phosphoric acid ester. 4 . The interlayer adhesive according to claim 3 , wherein a concentration of the phosphoric acid ester in the resin layer is 0.1% by mass or more. 5 . The interlayer adhesive according to claim 4 , wherein a concentration of the phosphoric acid ester in the resin layer is 0.5% by mass or less. 6 . The interlayer adhesive according to claim 3 , wherein the phosphoric acid ester has an HLB of 10 or less. 7 . The interlayer adhesive according to claim 3 , wherein the phosphoric acid ester has a polyoxyalkylene alkyl ether group.
8. The interlayer adhesive according to claim 7, wherein the polyoxyalkylene alkyl ether group is a compound represented by formula (1), R1 is an alkyl group having 8 to 18 carbon atoms, R2 is an alkylene group having 2 to 6 carbon atoms, n is 1 to 10, and * represents a bond.
9. The interlayer adhesive according to any one of claims 3 to 8, wherein the phosphate ester is a compound represented by formula (2) or formula (3), R1 is an alkyl group having 8 to 18 carbon atoms, and n is 1 to 10. 10 . The interlayer adhesive according to claim 3 , wherein the phosphoric acid ester has a dodecyl group. 11 . The interlayer adhesive according to claim 1 , wherein the polyvinyl acetal resin is a polyvinyl butyral resin. 12 . The interlayer adhesive according to claim 1 , wherein the resin layer contains a plasticizer. 13 . An interlayer adhesive for a touch panel, comprising the interlayer adhesive according to claim 1 . 14 . A touch panel comprising the interlayer adhesive according to claim 1 .
Citation Information
Patent Citations
Interlayer filling material for touch panels, and touch panel laminate
WO2016186029A1